Authentic Assessment Analysis of educational Learning Islamic Religion Junior High School in the Merdeka Curriculum - Poncokaryo, Munirotul Mahmuda; Setosa, A. Rosyid; Zuhriyah, Indah Aminatus (Edumaspul: Jurnal Pendidikan, 2023)
The Merdeka Curriculum is something that has recently emerged and implemented, not many educators are familiar with its practices, including in terms of assessment. Authentic assessment in learning Islamic Religious Education at the junior high school. It is important to do this to understand the effectiveness and success of the Merdeka curriculum in achieving the objectives of Islamic religious education. By conducting this analysis, the advantages and disadvantages of the authentic assessment used can be identified, as well as providing guidance for educators in developing better evaluation methods. This research method is Descriptive Qualitative which emphasizes literature (library reaserch) by collecting references related to evaluation/assessment which is then continued with the author's knowledge which is associated with what happens in the field and then peeling it with the Descriptive-analytic method. The results of this study are that the Merdeka curriculum emphasizes the profile of Pancasila students, the objectives of PAI subjects are emphasized on knowledge of Islamic values, PAI learning outcomes are related to 5 elements, namely Al-Qur'an Hadith, Akidah, Akhlak, Jurisprudence and Islamic Cultural History, Authentic Assessment of the Merdeka curriculum in PAI lessons consists of 3 aspects, namely 1) Cognitive: Written Tests, Oral Tests and Assignments, 2) Effective: attitude portfolio, class discussion, social project, writing product assessment, role simulation, self-assessment, open questions, reflection and feedback, 3) Psychomotor: Direct Observation, product assessment, simulation and skill portfolio. The three aspects are closely related because PAI is a lesson with the aim of practicing in everyday life, it is not enough just to have a theory (Knowledge) It needs field practice.